2016
DOI: 10.3390/en9050312
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dissolved Gases in Mineral and Vegetable Insulating Oils under Typical Electrical and Thermal Faults

Abstract: Dissolved gas analysis (DGA) is attracting greater and greater interest from researchers as a fault diagnostic tool for power transformers filled with vegetable insulating oils. This paper presents experimental results of dissolved gases in insulating oils under typical electrical and thermal faults in transformers. The tests covered three types of insulating oils, including two types of vegetable oil, which are camellia insulating oil, Envirotemp FR3, and a type of mineral insulating oil, to simulate thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Under the action of thermal stress in the ternary complex oil/paint/cellulose/Cu system, in addition to the oxygen-consuming thermo-oxidation processes, occur a series of complex gases-forming processes such as CO 2 and CO (oxidation of organic components H 2 , CH 4 , C 2 H 4 , C 2 H 6 etc. [24][25][26][27][28][29][30][31][32][33][34]. The results obtained by gaschromatography on the investigated oils, respectively the evolution during the thermal treatment at 130 o C of total content in în CO 2 , CO, H 2 , CH 4 , C 2 H 4 and C 2 H 6 -are presented synthetically in figure 8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the action of thermal stress in the ternary complex oil/paint/cellulose/Cu system, in addition to the oxygen-consuming thermo-oxidation processes, occur a series of complex gases-forming processes such as CO 2 and CO (oxidation of organic components H 2 , CH 4 , C 2 H 4 , C 2 H 6 etc. [24][25][26][27][28][29][30][31][32][33][34]. The results obtained by gaschromatography on the investigated oils, respectively the evolution during the thermal treatment at 130 o C of total content in în CO 2 , CO, H 2 , CH 4 , C 2 H 4 and C 2 H 6 -are presented synthetically in figure 8.…”
Section: Resultsmentioning
confidence: 99%
“…Under the practical conditions of operation, under the synergic action of thermal and electric stress, complex interactions between the components of the system leads to a series of processes such as: degradation of electroinsulating paper [1][2][3][4][5][6][7][8][9][10][11], corrosion of metal components, especially copper, with the formation of the products of corrosion that substantially reduces the insulation resistance and dielectric rigidity of the electro-insulating fluid [12][13][14][15][16][17][18][19], the formation of furans products (toxic products determined and monitored by various techniques) [3,8,[20][21][22][23], formation of the inert gases such as CO 2 as well as flammable as H 2 , CH 4 , C 2 H 4 , C 2 H 6 etc. [24][25][26][27][28][29][30][31][32][33][34].…”
mentioning
confidence: 99%
“…Xiang et al [4] also presented a comparison study of the formation of dissolved gases in mineraland vegetable-insulating oils. The authors used four interpretation dissolved gas analysis (DGA) methods and they confirmed that the diagnosis methods developed for mineral oil were not suitable for the diagnosis of electrical and thermal faults in vegetable-insulating oils and needed some modification.…”
Section: A Review Of the Special Issuementioning
confidence: 99%
“…Due to its complexity and importance, the problems of aging degree of paper insulation has been object of study in many recent works [2][3][4]. Several other tests of insulation items have been an important part of transformers fault diagnosis systems, with emphasis on chromatographic oil-dissolved gas analysis, namely dissolved gas analysis (DGA) [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%